Propuesta desarrollo del turismo vivencial en el centro poblado comunidad Kechwa Waycu del distrito de Lamas - Bartra Leveau, Cindy Lorena (2005)
The present research is called: "Development of Living Tourism in the Wayku Kechwa Community in Lamas district. The general objective is" to explain the characteristics of Living Tourism as a new, bold and attractive alternative to sustainable tourism in order to enjoy the ethnical, cultural and natural richness of the Wayku Kechwa Community in Lamas district whilst being a factor that improves their lifestyle. The specific objectives are as follows: "To diagnose the capacities and tourist potential in the Wayku Kechwa Community that can be developped as Living Tourism". "To explain the processes of implementing the Living Tourism in families of the Wayku Kechwa Community and to determine the tourist activities that Wayku Kechwa Community can offer as a part of Living Tourism". Living Tourism is introduced as a tool for development in communities. This due to rapid changes which have taken place in the world. Tourists' consumption habits have varied noticeably; they no longer just want to observe. Now, they want to have contact with nature and live experiences of the community that they visit. lt is an activity that is experienced at first hand and supports local agriculture so that both (Tourist and receptive community) benefit from each other. According to the OMT, this activity allows the conservation of environment, it creates new jobs, encourages popular customs and revalues cultural patrimony. Living Tourism is one type of rural tourism, where the community's population becomes teachers for the visitors, and in this way tourist are able to learn simple things that they have never done before, for instance, preparation of dye, breeding animals, fabric, elaboration of ceramics and agriculture.